2009
DOI: 10.1002/jbm.b.31465
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory suppression by endodontic sealers after aging 12 weeks In vitro

Abstract: Dental endodontic sealers are in intimate contact with tissues around the root apex (periapical area) for extended periods. New endodontic sealers have been developed in the past decade, but the biological responses to many new products are not well documented. In this study, we assessed in vitro monocytic cytotoxic and inflammatory responses to several contemporary endodontic sealers. AH-Plus (AH), Pulp Canal Sealer (PC), Epiphany (EPH), Endo-Rez (ER), and an experimental Endo-Rez (ERx) were initially placed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
22
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 55 publications
6
22
1
Order By: Relevance
“…Thereby, in contrast to the present findings, Brackett et al . () indicated that AH Plus exhibited no immunological response on THP‐l monocyte cell determined TNF‐α, IL1‐β and IL‐6. Such difference might be attributed to different cell‐lineage tested.…”
Section: Discussionmentioning
confidence: 98%
“…Thereby, in contrast to the present findings, Brackett et al . () indicated that AH Plus exhibited no immunological response on THP‐l monocyte cell determined TNF‐α, IL1‐β and IL‐6. Such difference might be attributed to different cell‐lineage tested.…”
Section: Discussionmentioning
confidence: 98%
“…Although clinically relevant, freshly mixed sealers were not studied because previous studies have shown that they are uniformly cytotoxic in vitro, 9,10 making a change in secretion of inflammatory mediators difficult to measure. 11,24,25 The assumption of this strategy was that eluted components from the materials would change with time; previous studies with other materials suggest that elution from sealers decreases or stays the same with time. 11,28 The major goals of endodontic therapy are to remove infected soft and hard tissues and to seal the canal space against ingress of bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…11,24,25 The assumption of this strategy was that eluted components from the materials would change with time; previous studies with other materials suggest that elution from sealers decreases or stays the same with time. 11,28 The major goals of endodontic therapy are to remove infected soft and hard tissues and to seal the canal space against ingress of bacteria. These goals are in place because of reports that failure of endodontic therapy is often caused by residual or invading bacteria that trigger inflammation and tissue destruction via secreted toxins including lipopolysaccharide (LPS).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations